1982
DOI: 10.1021/ma00229a002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and polymerization of 2,6,7-trioxabicyclo[2.2.2]octane and its derivatives

Abstract: Ten new 2,6,7-trioxabicyclo[2.2.2]octane derivatives, RC(OCH2)&R' [where R = H, R' = NOz R = H, R' = CH;OSO2C7H, (10); R CH3, R' = COOCH, (13); R = CH3, R' = COOC2H5 (14); R = CH,, R' = NO2 (15); and R = CH3, R' = NH2 (1611, were synthesized, and six other derivatives, 1-4, 11, and 12, were prepared by literature directions. Each of these bicyclic compounds was polymerized with boron trifluoride etherate as initiator at 0 "C. The polymers were usually obtained as highly crystalline white powders with high melt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…They are synthesized from condensation of triols with ethyl orthoformate, again removing the bicyclic monomer as it forms [61][62][63][64][65][66]. This topic has been reviewed [42][43][44]67].…”
Section: Orthoesters (54-57)mentioning
confidence: 99%
See 1 more Smart Citation
“…They are synthesized from condensation of triols with ethyl orthoformate, again removing the bicyclic monomer as it forms [61][62][63][64][65][66]. This topic has been reviewed [42][43][44]67].…”
Section: Orthoesters (54-57)mentioning
confidence: 99%
“…This topic has been reviewed [42][43][44]67]. [64] O O O 56 [65,66] O O 57 [65] O For the bicyclic acetals and orthoesters, oxonium ion propagation is still predominant. However, for these monomers, cleavage of the oxonium ion to oxacarbenium ion can lead to loss of stereoregularity [67].…”
Section: Orthoesters (54-57)mentioning
confidence: 99%
“…After the mixture was stirred for 24 h, it was quenched by the addition of triethylamine (3 drops). EtBOE was isolated by preparative HPLC (Japan Analytical Industry LC-908 system, equipped with two polystyrene gel columns (JAI gels H1, H2) using CHCl 3 as an eluent at a flow rate of 3.8 mL/min) from the mixture: yield 62 mg (43%); 1 H-NMR (400 MHz, CDCl 3 ) ␦ 5.5 (s, 1H), 3.9 (s, 6H), 1.3 (q, J ϭ 8.14 Hz, 2H), 0.8 (t, …”
Section: Depolymerization Of Poly(etboe)mentioning
confidence: 99%
“…Hall et al have reported that bicyclo ortho esters (BOEs) undergo single ring-opening polymerization at low temperature 3 and double ring-opening polymerization at high temperature. However, the detailed polymerization behavior of BOEs is not clear yet, much less the equilibrium character of the polymerization.…”
mentioning
confidence: 99%
“…High molecular weight polymers are favorable for practical use from the view point of physical property. In general, it is difficult to obtain high molecular weight polymers from BOEs due to main chain fission during the polymerization [5][6][7] . This problem may be overcome by copolymerization of BOEs with other monomers.…”
Section: Introductionmentioning
confidence: 99%